Correction to: At the US Epicenter of the COVID-19 Pandemic, an Orthopedic Residency Program Reorganizes. (November 2020) - Morse, Kyle W.; Wessel, Lauren E.; Premkumar, Ajay; James, Evan W.; Anatone, Alex J.; Barth, Kathryn; Bovonratwet, Patawut; Jordan, Yusef; Retzky, Julia; Suhardi, Vincentius; Thacher, Ryan; Uppstrom, Tyler; et al.
The published article contained four sentences with incorrect reference citations. Here, those sentences and the reference list are corrected.